2018
DOI: 10.3201/eid2412.172060
|View full text |Cite
|
Sign up to set email alerts
|

Capnocytophaga canimorsus Capsular Serovar and Disease Severity, Helsinki Hospital District, Finland, 2000–2017

Abstract: We assembled a collection of 73 Capnocytophaga canimorsus isolates obtained from blood cultures taken from patients treated at Helsinki University Hospital (Helsinki, Finland) during 2000–2017. We serotyped these isolates by PCR and Western blot and attempted to correlate pathogen serovar with patient characteristics. Our analyses showed, in agreement with previous research, that 3 C. canimorsus serovars (A–C) caused most (91.8%) human infections, despite constituting only 7.6% of isolates found in dogs. The 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Apart from the shared indicators, oropharyngeal pathogenic bacteria Capnocytophaga and Actinomyces were also identified as indicators of the gut microbial community type II (Figs. 1 d and 2d ) 30 , 31 . Because community types II and III often appeared in the early stage of COVID-19 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the shared indicators, oropharyngeal pathogenic bacteria Capnocytophaga and Actinomyces were also identified as indicators of the gut microbial community type II (Figs. 1 d and 2d ) 30 , 31 . Because community types II and III often appeared in the early stage of COVID-19 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the shared indicators, oropharyngeal pathogenic bacteria Capnocytophaga and Actinomyces were also identified as indicators of the gut microbial community type II (Figs. 1d and 2d) 28,29 . Because community types II and III often appeared in the early stage of COVID-19 (Figs.…”
Section: Bacteria–bacteria Co-occurrence Networkmentioning
confidence: 99%
“…Three C. canimorsus serovars (A-C) cause most human infections. 5 Hess et al first reported who determine the C. canimorsus serovar by PCR; 6 this test is not performed routinely in our laboratory, and should not be performed for our patient. It is a commensal bacterium of the oral cavities of dogs and cats.…”
Section: Discussionmentioning
confidence: 99%